Characterization and functional prediction of the dental plaque microbiome in patients with alveolar clefts - Zhang, Yuehua; Zhi, Qiang; Shi, Jiajun; Jin, Zehua; Zhou, Zhuojun; Chen, Zhenqi (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Alveolar cleft (AC) is a common congenital defect in people with cleft lip and palate (CLP). Alveolar bone grafting (ABG) is typically performed during adolescence, resulting in the fissure remaining in the mouth for a longer length of time. Patients with AC have a greater rate of oral diseases such as dental caries than the normal population, and the precise characteristics of the bacterial alterations caused by AC are unknown. Methods We recruited a total of 87 subjects and collected dental plaque samples from AC adolescents (AAP), post-operative ABG adolescents (PAP), healthy control adolescents (CAP), AC young adults (AYP), post-operative ABG young adults (PYP), and healthy control young adults (CYP). The sequencing of 16S rRNA genes was performed. Results The microbial composition of plaque from alveolar cleft patients differed significantly from age-matched healthy controls. Linear discriminant analysis effect size (LEfSe) analysis revealed that AAP was enriched for Neisseria, Haemophilus, Fusobacterium, Rhodococcus, Aggregatibacter, Gemella, and Porphyromonas, whereas AYP was enriched for Capnocytophaga, Rhodococcus, and Actinomyces-f0332. There were phenotypic differences in facultatively anaerobic, Gram-negative, Gram-positive, and oxidative stress tolerance between the AYP group with longer alveolar cleft and the healthy control group according to Bugbase phenotypic predictions. Alveolar bone grafting did not alter the functional phenotype of alveolar cleft patients but reduced the number of differential genera between alveolar cleft patients and healthy controls at both ages. Conclusions Our study systematically characterized the supragingival plaque microbiota of alveolar cleft patients, post-alveolar bone grafting patients, and matched healthy controls in two ages to gain a better understanding of plaque ecology and microbiology associated with alveolar clefts.